Estimating Selection Models without Instrument with Stata - Xavier D'Haultfœuille; Arnaud Maurel; Xiaoyun Qiu; Yichong Zhang (Institute of Labor Economics (IZA), 2019)
This article presents the eqregsel command for implementing the estimation and bootstrap inference of sample selection models via extremal quantile regression. The command estimates a semiparametric sample selection model without instrument or large support regressor, and outputs the point estimates of the homogenous linear coefficients, their bootstrap standard errors, as well as the p-value for a specification test.
Keywords: C21; C24; C87; J31; 330; extremal quantile regressions; sample selection models; eqregsel